Carbon‐Nanosheet Based Large‐Area Electrochemical Capacitor that is Flexible, Foldable, Twistable, and Stretchable. Issue 43 (24th March 2018) - Jun, Jong Han; Song, Hyeonjun; Kim, Changsoon; Choi, In‐Suk; Jeong, Youngjin; Lee, Ji‐Hoon
Abstract: With the growing demand for wearable electronics, developing new compatible energy systems is a prominent topic of research. Energy systems mounted on wearable electronics should exhibit high cost efficiency, mechanical robustness, and high electrochemical activity. Herein, all‐carbon‐based large‐area nanocomposites for freely deformable electrochemical capacitors are suggested to address these requirements. The three‐dimensionally integrated, self‐supported nanocomposites consist of activated carbons (ACs) distributed in direct spinning‐derived carbon nanotube (DS‐CNT) sheets without any additives, including conducting agents or binders. Owing to synergetic effects of the highly porous AC particles, high electron transport kinetics of CNTs, and facile ion accessibility resulting from acid treatment, the nanocomposites show a greatly improved specific capacitance of 128 F g −1, compared to that of pristine ACs (62 F g −1 ), based on the total mass of the electrodes. The exceptional mechanical stability of the nanocomposites, which are attached on prestretched elastomer substrates, is confirmed; only a ≈15% increase in the electrical resistance is observed under a tensile strain of 100%, and the initial resistance is fully recovered after releasing. Finally, the outstanding durability and electrochemical performance of the deformable all‐carbon‐based symmetric capacitors under various mechanical deformations of bending, folding, twisting, and stretching are successfully demonstrated. Abstract : A new type of mechanically robust electrochemical capacitor for wearable electronics based on all‐carbon‐based self‐supported nanocomposites is suggested. By optimizing the architecture of the 3D nanocomposite structure with activated carbons uniformly embedded in carbon nanotube sheets, outstanding durability and electrochemical performances are demonstrated under extreme mechanical deformations of bending, folding, twisting, and stretching.